2022
DOI: 10.1021/acs.jmedchem.1c02002
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Triazolone Derivatives as Potent PPARα/δ Dual Agonists for the Treatment of Nonalcoholic Steatohepatitis

Abstract: Peroxisome proliferator-activator receptors α/δ (PPARα/δ) are regarded as potential therapeutic targets for nonalcoholic steatohepatitis (NASH). However, PPARα/δ dual agonist GFT-505 exhibited poor anti-NASH effects in a phase III clinical trial, probably due to its weak PPARα/δ agonistic activity and poor metabolic stability. Other reported PPARα/δ dual agonists either exhibited limited potency or had unbalanced PPARα/δ agonistic activity. Herein, we report a series of novel triazolone derivatives as PPARα/δ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…However, it was limited by poor metabolic stability due to the hydrolysis of the ester group, which was critical for inhibitory activity. The significantly decreased inhibitory activity of compound 1e (Scheme ) proved the importance of the ester group . Considering this, the amide group was taken as an alternative (compound 1 ) since it was much more stable than the corresponding ester group.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, it was limited by poor metabolic stability due to the hydrolysis of the ester group, which was critical for inhibitory activity. The significantly decreased inhibitory activity of compound 1e (Scheme ) proved the importance of the ester group . Considering this, the amide group was taken as an alternative (compound 1 ) since it was much more stable than the corresponding ester group.…”
Section: Resultsmentioning
confidence: 98%
“…The metabolic stability studies were performed with our previously reported method. 33 Briefly, the spiking solution containing human liver microsomes (0.75 mg/mL) was incubated in a 96-well sample plate with the compounds (1 μM) at 37 °C. The reactions were stopped at different time points (0, 5, 15, 30, 45, and 60 min).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elafibranor (GFT505) is a PPARα/δ agonist, which can effectively improve insulin sensitivity, glucose homeostasis, and lipid metabolism, reduce inflammation, and has been considered a potential drug for NASH [27]. Cariou confirmed that elafibranor has significant effects in reducing triglycerides, fasting blood glucose, increasing high-density lipoprotein, and improving insulin resistance.…”
Section: Pparα/δ Agonist Elafibranormentioning
confidence: 99%
“…Oxidation of (+)- 12 with oxygen using Ma’s Fe-catalyzed protocol gave (+)- 16 in 95% yield and 92% ee. Subsequently, Horner–Wadsworth–Emmons (HWE) olefination of (+)- 16 with benzyl 2-(dimethoxyphosphoryl)­acetate ( 18 ) followed by a sequence of hydrogenations catalyzed by Ir-black , and Pd/C, respectively, and selective reduction of the resulting carboxyl group with BH 3 afforded (+)- 11 in three steps with 52% yield.…”
mentioning
confidence: 99%